Nitride-based light emitting diodes with Si-doped In0.23Ga0.77N - Kuo, C.H (IEEE Transactions on electron devices)
The electrical properties of Si-doped n+-In0.23Ga0.77N/GaN SPS structure were investigated and compared with conventional Mg-doped GaN contact layer. Temperature dependent Hall measurement showed that such a SPS structure exhibits a high sheet electron concentration. It was found that we could reduce the 20 mA LED forward voltage from 3.78 V to 2.94 V and also reduce the series resistance of the LED from 41 Ω to 10 Ω by introducing such an n+-InGaN/GaN SPS top contact. It was also found that we could improve the LED lifetime by such a SPS structure.